Etiquettes Of Tawakkul In Scientific Research Writing: A Linguistic and Thematic Qur’ānic Study/ آداب التوكّل على الله تعالى في كتابة البحث العلمي: دراسة قرآنية لغوية موضوعية - Abdelali Bey Zekkoub; Khaled Nabawi Suliaman; Yaser Annajr (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Islam places great emphasis on reliance on Allāh (Tawakkul), elevating it to one of the highest ranks of true monotheism, as the Qur’ān states: “And upon Allāh let the believers rely” (Āl ʿImrān 3:122). Without Tawakkul, human actions including scientific research cannot attain their full spiritual and ethical value. In the context of research, Tawakkul functions as both a spiritual and a methodological principle that guides the researcher, enhances the quality of scholarly work, strengthens ethical commitment, and motivates the production of beneficial and impactful knowledge that serves the individual, society, and the wider community, while seeking the pleasure of Allāh. However, the insufficient Qur’ānic grounding and limited practical application of Tawakkul in contemporary academic practice have contributed to various methodological shortcomings and unethical research practices. Accordingly, this study seeks to define Tawakkul in the context of scientific research, to derive its practical etiquettes from the Qur’ān, and to relate them to contemporary academic practice. Employing an inductive analytical approach to relevant Qur’ānic texts and a deductive method for deriving applicable guidelines, the study defines Tawakkul as reliance upon Allāh while taking legitimate means, exerting sustained effort, maintaining diligence, and pursuing both divine pleasure and societal benefit. It identifies twenty ethical guidelines organized into three domains: psychological, methodological, and ethical. Emphasizing that adherence to these etiquettes enhances research integrity, helps prevent plagiarism and academic misconduct, elevates the quality and standing of scientific research, and ensures the continuity of its scholarly and ethical impact.